Tackling the illegal practice of under-reporting employees' wages: Lessons from the Republic of Macedonia - Colin C. Williams; Slavko Bezeredi (UTMS Journal of Economics, 2017)
Recently, there has been growing recognition that some formal employees receive from their formal employers two wages, namely an official declared wage plus an additional undeclared (envelope) wage, which reduces the tax and social contributions paid to the authorities. The aim of this paper is to evaluate two competing approaches for tackling this illegal practice, namely a conventional rational economic actor deterrence approach which increases the penalties and risks of detection, and an emergent social actor approach that seeks to improve tax morale. To do this, a 2015 nationally representative survey comprising 2,014 face-to-face interviews conducted in FYR of Macedonia is reported. The finding is that 13 per cent of employees surveyed received under-reported wages by an amount that averaged 39 per cent of their net salary, and that in just under half (46 per cent) of reported cases, employees are active instigators of such a wage arrangement. Logit regression analysis reveals no association between employees receiving under-reported wages and the perceived level of penalties and risk of detection, but a strong association with the level of tax morale. The theoretical and policy implications are then discussed.
Keywords: H26; J46; K42; O17; P37; 330; envelope wages; tax morale; informal economy; tax evasion; Southeast Europe